Maximizing Symmetry in Upper Blepharoplasty: The Role of Microptosis Surgery. Issue 2 (February 2016) - Lew, Helen; Goldberg, Robert Alan
Abstract : Background: Traditional descriptions of blepharoplasty and ptosis surgery focus on the incision and eyelid crease. However, it may be more useful to consider the tarsal platform show as the important construct in analyzing and planning aesthetic eyelid surgery. Methods: In order to measure and characterize the key contours of the eyelid, the authors find it helpful to consider the brow fat span, tarsal platform show, and margin reflex distance. Results: Subtle eyelid ptosis can result in asymmetry by lengthening the tarsal platform show, and it is exacerbated by the tendency for the eyebrow to compensate. When ptosis is asymmetric, the plan should usually include asymmetric ptosis surgery. There are two general patterns that can be recognized and used for planning to address preoperative tarsal platform show asymmetry. If the tarsal platform show is longer on the side with worse blepharoptosis, then asymmetric or unilateral ptosis surgery will improve symmetry. In the cases of symmetric show despite asymmetric blepharoptosis, there may be bony and soft-tissue asymmetry, which leads to crowding of the orbit on the more ptotic side. Surgical planning should include consideration to increase the tarsal platform show on the more crowded side. It is not necessary to cut the eyelid skin in order to alter the tarsal show and brow fat span; ptosis surgery alone, by altering the eyelid position and eyebrow compensation, can reset the tarsal platform show/brow fat span relationship. Conclusions: It is important to recognize preoperative asymmetry, to predict the resetting of compensatory mechanisms, and to design asymmetric surgery, in order to maximize postoperative symmetry.